Let's make Padu a solid base for growth - Mohd Adnan, Normala (New Straits Times Press (M) Bhd, 2024)
The issues surrounding the Central Database Hub (Padu), which aims to consolidate socio-economic data, have generated a tidal wave of excitement and apprehension. While the concerns raised by critics deserve consideration, dismissing Padu's potential would be a disservice to our nation. Padu's goal to centralise and integrate data is commendable.